Correlations of Motion Characteristics and Kinematic Attributes of Fresh and Frozen-thawed Spermatozoa of Gir Bulls - Pathak, PK; Dhami, AJ; Chaudhri, DV (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
This investigation was carried out on semen of three healthy mature breeding bulls of Gir breed to evaluate the interrelationshipsamong sperm quality attributes of fresh and frozen-thawed semen assessed by Biovis CASA. The ejaculates (n = 24) having >75% initialmotility were diluted @80 million sperm/mL using TFYG extender, filled in French mini straws, and were frozen using a programmablebio freezer after 4 hours of equilibration. The straws were thawed in a water bath at 37°C for 30 sec. The freshly diluted and frozenthawed samples were assessed for routine subjective tests and various motion characteristics/kinematics by Biovis CASA. The Pearson’scorrelations for sperm motility and velocity/kinematic parameters of total motile sperm as well as of progressively motile sperm werestudied in freshly diluted and frozen-thawed semen. In fresh semen, total motile sperm assessed by CASA had significant (p
Keywords: CASA; Fresh and frozen-thawed sperm; Gir bull; Interrelationships; Kinematics; , Motion characteristics